2022
DOI: 10.1084/jem.20220638
|View full text |Cite
|
Sign up to set email alerts
|

Potent human broadly SARS-CoV-2–neutralizing IgA and IgG antibodies effective against Omicron BA.1 and BA.2

Abstract: Memory B-cell and antibody responses to the SARS-CoV-2 spike protein contribute to long-term immune protection against severe COVID-19, which can also be prevented by antibody-based interventions. Here, wide SARS-CoV-2 immunoprofiling in Wuhan COVID-19 convalescents combining serological, cellular, and monoclonal antibody explorations revealed humoral immunity coordination. Detailed characterization of a hundred SARS-CoV-2 spike memory B-cell monoclonal antibodies uncovered diversity in their repertoire and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 118 publications
2
32
0
Order By: Relevance
“… 1 Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) boosts mucosal IgA responses, 2 and neutralizing IgA, including neutralizing IgA against the B.1.1.529 (omicron) variant of SARS-CoV-2, has been detected after infection with wild-type SARS-CoV-2. 3 However, the potential role of mucosal IgA in protection against SARS-CoV-2 infection is still largely unknown.…”
mentioning
confidence: 99%
“… 1 Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) boosts mucosal IgA responses, 2 and neutralizing IgA, including neutralizing IgA against the B.1.1.529 (omicron) variant of SARS-CoV-2, has been detected after infection with wild-type SARS-CoV-2. 3 However, the potential role of mucosal IgA in protection against SARS-CoV-2 infection is still largely unknown.…”
mentioning
confidence: 99%
“…The high IgA titers against HR1 are intriguing. Interestingly, although IgG are about five times more abundant in serum than IgA, several studies showed higher neutralizing activities for IgA purified from sera of infected individuals compared to their IgG counterparts [64] , [65] . Whether IgA against HR1 display neutralizing function will need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…It is intriguing why the neutralization activity induced by T4-CoV-2 vaccination is so broad. The reasons for this finding require further investigation, especially if it relates to the presence of high levels of IgA in the serum and sIgA in BALF, which are reported to be more potent than IgG in neutralizing SARS-CoV-2 virus ( 14 , 64 ).…”
Section: Discussionmentioning
confidence: 99%